Reliability of subjective pain ratings and nociceptive flexion reflex responses as measures of conditioned pain modulation - Jurth, Carlo (Pulsus Group Inc, 2014)
BACKGROUND: The endogenous modulation of pain can be assessed through conditioned pain modulation (CPM), which can be quantified using subjective pain ratings or nociceptive flexion reflexes. However, to date, the test-retest reliability has only been investigated for subjective pain ratings. OBJECTIVE: To compare the test-retest reliability of CPM-induced changes, measured using subjective pain ratings and nociceptive flexion reflexes, to provide a reliable scoring parameter for future studies. METHOD: A total of 40 healthy volunteers each received painful electrical stimuli to the sural nerve to elicit nociceptive flexion reflexes. Reflex sizes and subjective pain ratings were recorded before and during the immersion of the contralateral hand in hot water to induce CPM as well as innocuous water as control. Measurements were repeated in a retest 28 days later. RESULTS: Intraclass correlation coefficients showed good test-retest reliabilities of CPM during the hot water stimulus for both scoring parameters. Subjective pain ratings also correlated between test and retest during the control stimulus. CONCLUSIONS: Subjective pain ratings and nociceptive flexion reflexes show comparable test-retest reliabilities, but they reflect different components of CPM. While subjective pain ratings appear to incorporate cognitive influences to a larger degree, reflex responses appear to reflect spinal nociception more purely.